Microclimate effects and outdoor thermal comfort of green roof types in hot and dry climates: Modelling in the historic city of Yazd, Iran - Zahra Karimian; Sara Mahdizadeh (PLoS ONE, 2025)
In hot and arid climates, developing green roofs to improve the microclimate and thermal comfort faces challenges due to water scarcity and harsh climate conditions. To evaluate the effect of green roof types on microclimate parameters and thermal comfort, a simulation was conducted in Yazd, Iran, using the ENVI-met model. Three scenarios—intensive green roofs, extensive green roofs, and roofs without vegetation—were simulated using meteorological data from 7:00 am to 6:00 PM during the hottest period of the year. Desert-adapted plant species were included in two green roof types. The model outputs indicated that, compared to extensive green roofs and roofs without vegetation, intensive green roofs resulted in lower air temperature, mean radiant temperature, and longwave radiation. They also led to higher wind speed and relative humidity, contributing to more desirable thermal comfort. Extensive green roofs and roofs without vegetation generally showed no significant differences in the measured microclimatic parameters or thermal comfort index. As suggested by the findings of this study, intensive green roofs demonstrated superior performance in enhancing thermal comfort compared to extensive green roofs. However, during the hottest period of the year and within the measured hours, all three scenarios were classified as ‘very hot’ (PMV = 5.03) and ‘hot’ (PMV = 3.2), experiencing strong to extreme heat stress, respectively. The measured hours and distance from the roofs affected the microclimatic parameters and thermal comfort, with the intensive green roof showing the most favorable thermal comfort condition (PMV = 0.18) during 7:00–9:00 am, perceived as comfortable with no thermal stress. However, the microclimatic improvements and thermal comfort enhancements resulting from the simulated green roofs in the surrounding environment) were not significant. Considering the outcomes alongside the severe climatic conditions prevalent in the city of Yazd, characterized by high temperatures, intense radiation during the summer, and extreme water scarcity, the proposition for the construction and development of green roofs in this region is not advisable. Although green roofs aim to ameliorate the microclimate and improve thermal comfort during hot periods, their effectiveness under such harsh conditions remains limited.